Economies of Scale: Some Statistical Evidence - Moore, Frederick T. (Quarterly Journal of Economics, 1959)
I. Statement of the problem, 232. — II. The evidence from some previous studies, 233. — III. The “.6 factor” rule and its application, 234. — IV. Specific evidence in a selection of metal processing and chemical industries, 236. — V. Studies of selected mineral industries, 239. — VI. Conclusions, 242.